The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/fwb.12793
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the joint effects of flow regime, climatic variability and dispersal mode on beta diversity of riverine communities

Abstract: Summary Differences in the composition of ecological communities among rivers with contrasting flow regimes have been detected in many regions worldwide. However, we know little of how climatic variation alters these spatial patterns for constituent species with varying dispersal modes and strengths. We predicted that beta diversity (spatial variation in composition) of macroinvertebrate and fish assemblages among streams with near‐perennial, mildly intermittent and highly intermittent flow regimes would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 86 publications
(126 reference statements)
2
40
0
Order By: Relevance
“…, Rolls et al. ). However, persistent low‐flow conditions have caused long‐term changes in community structure where species adapted to low‐flow conditions expanded their range and increased in abundance with complementary reductions in species favored by high flows (Lawson and Johnston ).…”
Section: Discussionmentioning
confidence: 99%
“…, Rolls et al. ). However, persistent low‐flow conditions have caused long‐term changes in community structure where species adapted to low‐flow conditions expanded their range and increased in abundance with complementary reductions in species favored by high flows (Lawson and Johnston ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Rolls et al. () showed that prolonged droughts can lead to high regional community variability by decreasing connectivity and increasing environmental heterogeneity. The weaker explanatory power of environmental distance in IR during the rewetting period may result from an increase in stochastic processes.…”
Section: Discussionmentioning
confidence: 99%
“…In this Special Issue, we specifically seek to examine how IR ecology is maturing and how some key questions in ecology can be addressed through the study of IRs as highly dynamic ecosystems. We bring together 13 papers, including this introduction, spanning observational case studies (Corti & Datry, ; Datry, Bonada & Heino, ; Datry et al ., ; Marshall et al ., ; Rolls, Heino & Chessman, ; Siebers et al ., ; Stromberg & Merritt, ; Welter & Fisher, ; Whitney et al ., ), field (Vander Vorste, Malard & Datry, ) and laboratory (Stubbington et al ., ) experiments, and reviews (Leigh et al ., ).…”
Section: From Humble Beginnings the Future Of Ir Ecology Is Brightmentioning
confidence: 99%